STRATEGI PENGEMBANGAN PRODUK UMKM KECAMATAN BAYANG KABUPATEN PESISIR SELATAN DALAM MENHADAPI PERSAINGAN BISNIS - Amrullah, Amrullah; Yulihardi, Yulihardi; Malik, David; Afrida, Afrida (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
The purpose of this activity is to enhance the creativity and innovation of MSME (Micro, Small, and Medium Enterprises) actors and the local community through an analysis of product development strategies in examining opportunities and challenges. This includes knowledge about packaging, labeling, and branding of products, as well as improving business management, particularly in marketing and product quality enhancement. The impact of this activity is that participants gain insights into opportunities for MSME product development, acquire additional knowledge about the importance of MSME development strategies, and avoid complacency with their current production conditions. Products should not appear mediocre, unattractive, untidy, or unclean. To grow their businesses, entrepreneurs need to be innovative in product packaging. The team carried out this program through face-to-face meetings. The implementing team's hope is that participants will become more interested and motivated after receiving the training, aiming to improve and expand their MSME businesses. Keywords: Pengembangan Produk, UMKM, Nagari Sawah Laweh Kab. Pesisir Selatan